Factors Influencing Organisational Commitment and Adaptive Work Behaviour of the Digital Native Employees in Broadcasting Stations in Delta State, Nigeria - Onofere Princewill Okereka; Abraham Ejogba Orhero; Ugo Chuks Okolie (Ianna Journal of Interdisciplinary Studies, 2023)
Background: Employees from different generations differ in their habits, drives, and attitudes. Miscommunication, difficulty retaining top talent, high employee attrition, work-life conflict, and a decline in organisational loyalty are possible consequences of ineffective management of different generations. Most studies conducted on digital native employees to date have been conducted in developed countries that do not share distinctive cultural features with Nigeria.